Kepimpinan Spiritual Kiai dalam Meningkatkan Karakter Santri di Pondok Pesantren Darul Huda Blitar - Moh Ikhsani; Anis Zunaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine Kiai's spiritual leadership in an effort to improve the character of students. Using a qualitative approach, this research analyzes Kiai's role as a role model, spiritual guide, and motivator in shaping the character of students who are religious, have noble character, and achieve. The research results show that Kiai's spiritual leadership characteristics always adhere to the Vision and Mission in making decisions, carry out organizational culture by forming integration through comprehensive care and attention, forming a religious personality. Meanwhile, the spiritual leadership strategy is to generate a feeling of gratitude, provide motivation and invite synergy in running the organization in Islamic boarding schools. So that this spiritual leadership is effective and can create a learning environment that is conducive to the character growth of students. Effective leadership does not only depend on intelligence or technical skills, but also on the moral qualities of the leader himself and it is easier to build strong and trusting relationships with subordinates, colleagues and the community he leads.